Rat Trap Bond: A state of review - Bukhari, H. (Institute of Electrical and Electronics Engineers Inc., 2020)
Construction industry started to incorporate the idea of energy efficiency in infrastructure and design a few decades ago. This review paper specifically deals with one of such energy efficient masonry technique called Rat-trap bond. For this purpose, body of knowledge is explored high and low and only those articles are selected that deal particularly with Rat-trap bond. The thorough study of this selected literature shows that the bond is not only energy proficient but also cost saving. With the ability to reduce cooling and thermal load, the bond is structurally stable as well. The compressive strength test of rat-trap bond with C.M. 1:5 is 49 (0.87 MPa) stronger than C.M 1:4 (1.30 MPa) with and without roof slab respectively. The review is an attempt to suggest future recommendations by finding the research gap in this field of knowledge. It has been found that although the bond has a promising ability to be practically adopted yet it has not enjoyed the eminence it deserves. Only a limited number of case studies are present for realization of this technique. It is recommended that this masonry technique, owing to its less construction cost and excellent energy efficiency, can be primarily utilized by low income groups and in residential constructions. Â© 2020 IEEE.